Development of completely bio‐based epoxy networks derived from epoxidized linseed and castor oil cured with citric acid. (1st May 2018) - Sahoo, Sushanta K.; Khandelwal, Vinay; Manik, Gaurav
Abstract : Bio‐based epoxy resins were synthesized from nonedible resources like linseed oil and castor oil. Both the oils were epoxidized through in situ method and characterized via Fourier transform infrared and 1 H‐NMR. These epoxidized oils were crosslinked with citric acid without using any catalyst and their properties compared with diglycidyl ether of bisphenol A‐epoxy. The tensile strength and modulus of epoxidized linseed oil (ELO) were found to be more than those of epoxidized castor oil (ECO)‐based network. However, elongation at break of ECO was significantly higher than that of both ELO and epoxy, which reveals its improved flexibility and toughened nature. Thermogravimetric analysis revealed that the thermal degradation of ELO‐based network is similar to that of petro‐based epoxy. Dynamic mechanical analysis revealed moderate storage modulus and broader loss tangent curve of bio‐based epoxies confirming superior damping properties. Bioepoxies exhibit nearly similar contact angle as epoxy and display good chemical resistant. The preparation method does not involve the use of any toxic catalyst and more hazardous solvents, thus being eco‐friendly.